A New Approach to Vascular Screening: Identification of Impaired Vascular Function Using the FMSF Technique - Andrzej Marcinek; Joanna Katarzynska; Jerzy Gebicki (Sensors, 2024)
Arterial blood pressure monitoring plays an important role in preventive medicine, allowing, in selected cases, the identification of vascular dysfunction. In this review, we propose a new non-invasive approach to assessment of the circulatory system, based on its reaction to hypoxia induced by post-occlusive reactive hyperemia (PORH). Three key parameters can be used for vascular screening: the Reactive Hyperemia Response (RHR), which represents the overall reaction of the macro- and microcirculation to transient hypoxia; Hypoxia Sensitivity (HS), which reflects hypoxia-induced activation of myogenic oscillations of the microcirculation; and Normoxia Oscillatory Index (NOI), which characterizes microcirculatory oscillations under normoxia conditions. A method for assessing these parameters, analogous in simplicity to arterial blood pressure measurement, is provided by the Flow Mediated Skin Fluorescence (FMSF) technique. Reference values are proposed based on numerous test measurements.